Globale reaktioner på COVID-19 – religion og trossamfund i en krisetid - Riexinger, Martin; Thorsen, Jakob Egeris; Fibiger, Thomas Brandt; Borup, Jørn; Fibiger, Marianne Qvortrup (Religion i Danmark, 2021)
Globale reaktioner på COVID-19 – religion og trossamfund i en krisetid